1982
DOI: 10.1111/j.1600-051x.1982.tb02096.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between plaque accumulation and Langerhans cell numbers in the oral epithelium of attached gingiva

Abstract: After gingival health had been achieved in four subjects they were instructed to cease all oral hygiene measures. At 0, 8 and 21 days Plaque and Gingival Indices were recorded and gingival biopsies were removed from the buccal aspect of a first molar. Frozen sections of the gingival oral epithelium were stained for ATPase and 5'-nucleotidase to determine the number of Langerhans cells in a defined cross-sectional area. It was found that, as plaque accumulated, there was a statistically significant increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 28 publications
8
42
0
1
Order By: Relevance
“…S8) and, thus, might directly interact with RANKL-expressing CD4 + T cells. Although the impact of infiltrating CD4 + T cells on gingival LCs is unknown, the welldocumented reduction in LC numbers during human periodontitis could be a result of an imbalance in CD40L/RANKL expression by local CD4 + T cells (45)(46)(47). Gingival DCs might also regulate the function of T cells accumulating in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…S8) and, thus, might directly interact with RANKL-expressing CD4 + T cells. Although the impact of infiltrating CD4 + T cells on gingival LCs is unknown, the welldocumented reduction in LC numbers during human periodontitis could be a result of an imbalance in CD40L/RANKL expression by local CD4 + T cells (45)(46)(47). Gingival DCs might also regulate the function of T cells accumulating in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the term "follicle" might imply a proliferating B cell lymphoid organ and hence may be misleading, but nonetheless propose this terminology. We propose that the development of OLF is initiated in gingivitis by LCs homing to the gingival epithelium in response to bacteria/Ags in the oral biofilm (39), as well as a source of the earliest signals for lymphoid/ myeloid trafficking, i.e., epithelium/keratinocytes (40). That the CD1a ϩ cells enumerated in this study were in fact LCs was confirmed by scanning laser confocal microscopy and double immunofluorescence with CD1a and the LC-specific marker of Birbeck granules, LAG (41), as well as single immunoenzyme staining with langerin (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…1,22 Moreover, a large number of previous studies compared gingivitis and periodontitis. 2,4,6 In our understanding, this comparison is not correct because they are distinct periodontal diseases, with different inflammatory cells, cytokines, and pathogens. Moreover, in the majority of previous studies 4,23 , scaling and root planing and oral hygiene instructions were given only to the periodontitis patients, before tissue samples were removed, which would change the number of inflammatory cells.…”
Section: -21mentioning
confidence: 99%
“…2,4,6 In our understanding, this comparison is not correct because they are distinct periodontal diseases, with different inflammatory cells, cytokines, and pathogens. Moreover, in the majority of previous studies 4,23 , scaling and root planing and oral hygiene instructions were given only to the periodontitis patients, before tissue samples were removed, which would change the number of inflammatory cells. In this study, all inflammatory mononuclear plasma cells and lymphocytes were counted; thus, we can affirm that no changes in LC density were observed to be correlated with increased inflammation, which is in accordance with previous studies.…”
Section: -21mentioning
confidence: 99%
See 1 more Smart Citation